Enhanced stability designs of cell membrane chromatography for screening drug leads. Issue 14 (20th May 2022) - Fu, Jia; Jia, Qianqian; Liang, Peida; Wang, Saisai; Zhou, Huaxin; Zhang, Liyang; Wang, Hong; Gao, Chunlei; Lv, Yanni; Han, Shengli; He, Langchong
Abstract : Cell membrane chromatography is an effective method for screening bioactive components acting on specific receptors in complex systems, which maintains the biological activity of the membrane receptors and improves screening efficiency. However, traditional cell membrane chromatography suffers from poor stability, resulting in a limited life span and low reproducibility, greatly limiting the application of this method. To address this problem, cyanuric chloride‐decorated silica gel was used for the covalent immobilization of the cell membranes. Cyanuric chloride reacts with amino groups on the cell membranes and membrane receptors to form covalent bonds. In this way, the cell membranes are not easy to fall off. The column life of the cyanuric chloride‐decorated epidermal growth factor receptor/cell membrane chromatography column was extended to more than 8 days, whereas the column life of the normal cell membrane chromatography column dropped sharply in the first 3 days. A cyanuric chloride‐decorated epidermal growth factor receptor/cell membrane chromatography online HPLC‐IT‐TOF‐MSn system was applied for screening drug leads from Trifolium pratense L . One potential drug lead, formononetin, which acts on the epidermal growth factor receptor, was screened. Our strategy of covalently immobilizing cell membrane receptors also improved the stability of cell membrane chromatography.